The nature and extent of healthy architecture: the current state of progress. (15th July 2019) - Rice, Louis
Abstract : Purpose: The design of the built environment is a determinant of health. Accordingly, there is an increasing need for greater harmonization of the architectural profession and public health. However, there is a lack of knowledge on whether designers of the built environment are changing their practices to deliver healthier urban habitats. The paper aims to discuss these issues. Design/methodology/approach: The research uses a multi-method approach to data analysis, including: systematic mapping study, structured review and thematic analysis. Findings: The research finds that there are almost no requirements for the compulsory inclusion of health across institutions and agencies that have the power to execute and mandate the scope of architectural profession, training, education, practice or knowledge. Despite the urgent need for action and the myriad entreatments for greater integration between architecture and health, there is very little evidence progress. Practical implications: The research has implications for the architectural profession and architectural education. Health and well-being is not currently an integral part of the educational or professional training requirements for architects. University educational curriculum and Continuing Professional Development criteria need to better integrate health and well-being into their knowledge-base. Social implications: The design of the built environment is currently undertaken by an architectural profession that lacks specialized knowledge of health and well-being. There is a risk to society of environments that fail to adequately protect and promote the health and well-being of its inhabitants. Originality/value: The research evidences, for the first time, the lack of integration of "health and wellbeing" within the architecture profession training or education systems.